Increase of External Osmolarity Reduces Morphogenetic Defects and Accumulation of Chitin in a gas1 Mutant of Saccharomyces cerevisiae - Turchini, Anna (American Society for Microbiology, 2000)
We have performed a physiological analysis of the effects of high-osmolarity media on gas1Δ cells. The reductions in the duplication time, number of pluribudded cells, hypersensitivity to Calcofluor and sodium dodecyl sulfate, and chitin level indicate a partial suppression of the mutant phenotype. GAS1 deletion was found to be lethal in the absence of the Bck1 and Slt2 (Mpk1) proteins of the cell integrity pathway.